NRG1, PIP4K2A, and HTR2C as Potential Candidate Biomarker Genes for Several Clinical Subphenotypes of Depression and Bipolar Disorder - Levchenko, Anastasia; Vyalova, Natalia M.; Nurgaliev, Timur; Pozhidaev, Ivan V.; Simutkin, German G.; Bokhan, Nikolay A.; Ivanova, Svetlana A. (Frontiers in Genetics, 2020)
In the present study NRG1, PIP4K2A, HTR2C, GSK3B, BDNF, and NGF were analyzed by sequencing a cohort of 19 patients with bipolar affective disorder, 41 patients with recurrent depressive disorder, and 55 patients with depressive episode. A number of genetic variants were found to be associated with antidepressant treatment response, time to recurrence of episodes, and depression severity. Namely, alleles of rs35641374 and rs10508649 (NRG1 and PIP4K2A) may be prognostic biomarkers of time to recurrence of depressive and manic/mixed episodes among patients with bipolar affective disorder. Alleles of NC_000008.11:g.32614509_32614510del, rs61731109, and rs10508649 (also NRG1 and PIP4K2A) seem to be predictive biomarkers of response to pharmacological antidepressant treatment on the 28th day assessed by the HDRS-17 or CGI-I scale. In particular, the allele G of rs10508649 (PIP4K2A) may increase resistance to antidepressant treatment and be at the same time protective against recurrent manic/mixed episodes. These results support previous data indicating a biological link between resistance to antidepressant treatment and mania. Bioinformatic functional annotation of associated variants revealed possible impact for transcriptional regulation of PIP4K2A. In addition, the allele A of rs2248440 (HTR2C) may be a prognostic biomarker of disease severity among patients with depression. This allele decreases expression of the neighboring immune system gene IL13RA2 in the putamen according to the GTEx portal; this variant is near rs6318 (previously associated with mood disorders and response to antidepressant therapy) that is an eQTL for the same gene and tissue. Functional studies using cellular or animal models are warranted to support these results.